Affinity chromatography for vaccines manufacturing: Finally ready for prime time?. Issue 36 (23rd August 2019) - Zhao, Mochao; Vandersluis, Melissa; Stout, James; Haupts, Ulrich; Sanders, Matthew; Jacquemart, Renaud
Highlights: This paper reviews the success of affinity chromatography at lab scale for vaccine purification and assesses the challenges preventing its industrial implementation. Review of recent advancements in ligand development and chromatographic media indicates opportunity to bring affinity chromatography from lab bench to large-scale manufacturing. It is suggested that when combined with single-use technology, affinity chromatography can significantly simplify process architecture, improve productivity and flexibility, and reduce cost of goods. Abstract: Affinity chromatography is among the most powerful separation techniques, achieving the finest separation with high yields even in the most challenging feed streams. Incorporating affinity chromatography in vaccine purification has long been attempted by researchers to improve unit yield and purity with the secondary goal of reducing the number of downstream process operations. Despite the success in laboratory-scale proof of concept, implementation of this technique in pilot or cGMP manufacturing has rarely been realised due to technical and economic challenges in design and manufacturing of ideal ligands as well as availability of high-productivity chromatography media. This paper reviews evolving technologies in engineered ligands and chromatography media that are encouraging companies to re-visit the possible use of affinity chromatography in larger scale vaccine purification. It is postulated that commercial-scale implementation of high throughput single-use affinity chromatography can significantly simplify process architecture, improve productivity and flexibility, and reduce cost of goods.